Dinamika Self Concept Dalam Perspektif Psikologi Islam - Rahma Delviza; Agustri Sania; Tiva Munifah Jivi; Rika Dahlia; Mega Adyna Movitaria (Affection: Journal of Psychology And Counseling, 2024)
The purpose of this research is to determine the importance of understanding self-concept in developing a person's identity, including personality, experiences and social status, Self-concept also helps individuals to understand their inner beliefs and values. Self-concept is our overall perception of ourselves, including physical, social, and psychological aspects, based on our experiences and interactions with other people. A student's self-concept is very important in knowing their talents and solving problems both at school and outside of school, this also has a direct impact on students' learning motivation. Religion uses this as a tool of self-psychology and the existence of an expression that is observed by others can be called personality or morality. This research uses a literature review method which carries out analysis from various sources, including scientific papers, journal reviews. This research assessment method was carried out qualitatively, which means the author collected data in text form which was then analyzed descriptively. This research highlights the importance of self-concept in an Islamic psychology perspective highlighting the importance of understanding and studying self-concept in individuals.